The impact of primiparous self-efficacy on increasing maternal competence during the postpartum period - Al-Jarrah, Hanan; Kassab, Manal; Alzayyat, Abdulkarim (KHD-Production, 2025)
Commonly, primiparous are unfamiliar with the experience of dealing with a newborn, nor do they have the competence to take care of them. A high level of self-efficacy will increase maternal competence in dealing with the newborn. The study aimed to (1) determine the level of maternal sense of competence among primiparous women in Jordan, (2) determine the level of perceived maternal self-efficacy among primiparous women in Jordan, (3) determine whether a significant relationship exists between maternal sense of competence and perceived maternal self-efficacy, and (4) identify whether sociodemographic characteristics are significantly related with maternal sense of competence and perceived maternal self-efficacy. The study employed a cross-sectional, descriptive correlational research design. Recruitment was performed at the King Abdullah University Hospital. A total of 89 participants joined the study. The Maternal Efficacy Questionnaire (MEQ) measured the perceived maternal self-efficacy, and the Parenting Sense of Competence Scale (PSOCS) measured the maternal sense of competence. Participants had a moderate positive maternal sense of competence and a high level of perceived maternal self-efficacy. Age had a weak positive but significant relationship with a maternal sense of competence. No significant relationships were found between maternal sense of competence and perceived maternal self-efficacy. Maternal self-competence and self-efficacy are significant components that make up a mother's armamentarium to perform parenting skills and make decisions about child-rearing. However, no significant relationship was found between perceived maternal self-competence and maternal self-efficacy. Future research should explore what factors drive low self-competence and self-efficacy among primiparous women. Nurses can assist and support mothers in improving their perceived self-competence levels and help mothers sustain the already high levels of maternal self-efficacy. Interventions must be multidimensional and multidisciplinary, involving other specialties such as midwives, nurses, and breastfeeding counselors.